Infoboxes and cleanup tags: Artifacts of Wikipedia newsmaking. (January 2015) - Ford, Heather
Wikipedians use a number of editorial elements, including infoboxes and cleanup tags to coordinate work in the first stage of articles related to breaking news topics. When inserted into an article, these objects are intended to simultaneously notify editors about missing or weak elements of the article and to add articles to particular categories of work. This categorization practice enables editors to collaborate iteratively with one another because each object signals work that needs to be done by others in order to fill in the gaps of the current content. In addition to this functional value, however, categorization also has a number of symbolic and political consequences. Editors are engaged in a continual practice of iterative summation that contributes to an active construction of the event as it happens rather than a mere assembling of 'reliable sources'. The deployment and removal of cleanup tags can be seen as an act of power play between editors that affects readers' evaluation of the article's content. Infoboxes are similar sites of struggle whose deployment and development result in an erasure of the contradictions and debates that gave rise to them. These objects illuminate how this novel journalistic practice has important implications for the way that political events are represented.